Adsorption study of mango peel activated carbon as iron removal for batik waste industry - Nugroho, Agung; Amanah, Nur Layli; Firdaus, Revo Gilang (Jurnal Rekayasa Proses, 2022)
Mango peel waste which has a carbon functional group was converted to activated carbon. The as-synthesized activated carbon (AC) was then utilized as an adsorbent for batik waste which contains heavy metal substances such as Fe2+. The purpose of this study was to determine the optimum process variation in absorbing heavy metal ion Fe contained in batik waste. Four variation methods of activated carbon synthesis were explored to determine the most suitable method of AC synthesis. The results showed that the sample synthesized using a combination physical-chemical-physical process was the best process variation resulting in percentage removal of Fe2+ of 84.81%. FTIR showed that the functional groups in mango peel were visible for all variations of the process, namely hydroxyl (-OH) derived from cellulose and hemicellulose and carboxyl (-COOH) derived from pectin. The adsorption study showed that the most suitable isotherm for all process variations was Langmuir with an R2 value of 0.9999 for the MPAC-4 sample. The adsorption mechanism is physisorption with a value of E < 8 kJ/mol based on the D-R isotherm and has the largest adsorption capacity of Qmax 8.2 mg/g.